Pentingnya Peran Media Sosial dalam Pelaksanaan Misi di Masa Pandemi Covid-19 - Yonatan Alex Arifianto; Sari Saptorini; Kalis Stevanus (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2020)
The Coronavirus Disease 2019 (Covid-19) outbreak, or better known as the Corona virus, is spreading rapidly, bringing changes in socializing and communicating in the community. Government regulations require all citizens to participate in breaking the chain of transmission of the virus. This of course also has an impact on the concept and implementation of the mission that has been carried out, namely face to face. As one way the church must continue to take its role in witnessing or preaching the gospel of Jesus Christ to non-believers using social media as the right choice in carrying out missions during the Covid-19 pandemic. This article will describe the understanding of the Church or believers as recipients of God's mission mandate, and the use of social media as a means of carrying out missions during the Covid-19 pandemic, and how the effectiveness and constraints of carrying out missions through social media. The results of the research can be said that the mission can still be carried out in all conditions in the midst of society even though without having to meet face to face with the way the church empowers its people to actively use social media as a means of preaching the gospel.AbstrakWabah Coronavirus Disease 2019 (Covid-19) atau lebih dikenal dengan nama virus Corona yang menyebar dengan cepat membawa perubahan dalam bersosialisasi dan berkomunikasi di masyarakat. Aturan pemerintah mengharuskan semua warga berpartisipasi dalam memutus rantai penularan virus tersebut. Hal itu tentu juga berdampak pada konsep dan pelaksanaan misi yang selama ini dilakukan, yakni dengan tatap muka secara langsung. Sebagai salah satu caranya gereja harus tetap mengambil perannya untuk bersaksi atau memberitakan Injil Yesus Kristus kepada orang-orang yang belum percaya menggunakan media sosial sebagai pilihan yang tepat di dalamnya pelaksanaan misi di masa pandemi Covid-19.  Artikel ini akan memaparkan pemahaman tentang Gereja atau orang percaya sebagai penerima mandat misi Allah, dan  pemanfaatan media sosial sebagai salah satu sarana pelaksanaan misi di masa pandemi Covid-19, dan bagaimana efektivitas serta kendala pelaksanaan misi melalui media sosial. Hasil penelitian dapat dikatakan bahwa misi dapat tetap dilakukan dalam segala kondisi di tengah-tengah masyarakat meskipun tanpa harus tatap muka secara langsung dengan cara gereja memberdayakan umatnya untuk secara aktif menggunakan media sosial sebagai sarana pemberitaan Injil.